The Capacity of Artmaking Assemblages to Enable Positive Transformations: A Case of a Finnish Schoolgirl - Tumanyan, Marian (Art/Research International, 2024)
This article explores how artmaking assemblages bring changes in children’s potential to express themselves. Assemblages are a system consisting of human, non-human, material, and relational elements in a given situation. Through the concept of artmaking assemblage, I explore the arts-based effects emerging around a Finnish schoolgirl participating in artmaking research workshops. Analysed video data from the workshops illustrate how her expression and participation change in and through the artmaking assemblages, and how different details in the artmaking assemblages combine to promote those changes. The girl’s artworks are used as data, as is an interview with the artist who participated in the workshops. The concept of artmaking assemblage is used as a thinking and writing companion when analysing the events from the artmaking processes. I conclude that artmaking processes, when done in a consistent manner and in a trust-based environment, support children’s possibilities to express themselves around sensitive issues.